Critical Medical Anthropology in Midwifery Research: A Framework for Ethnographic Analysis. (19th October 2016) - Newnham, Elizabeth C.; Pincombe, Jan I.; McKellar, Lois V.
In this article, we discuss the use of critical medical anthropology (CMA) as a theoretical framework for research in the maternity care setting. With reference to the doctoral research of the first author, we argue for the relevance of using CMA for research into the maternity care setting, particularly as it relates to midwifery. We then give an overview of an existing analytic model within CMA that we adapted for looking specifically at childbirth practices and which was then used in both analyzing the data and structuring the thesis. There is often no clear guide to the analysis or writing up of data in ethnographic research; we therefore offer this Critical analytic model of childbirth practices for other researchers conducting ethnographic research into childbirth or maternity care.